Antiepileptic Drugs Impair Shortening of Isolated Cardiomyocytes - Hulbert, Johanna; Elger, Christian E.; Meyer, Rainer; Surges, Rainer (Frontiers in Neurology, 2017)
Background Most antiepileptic drugs (AEDs) inhibit seizure generation by acting on voltage-dependent ion channels. Voltage-dependent sodium and calcium channels are commonly expressed in brain and heart, suggesting that AEDs may have considerable cardiodepressive effects, thereby facilitating sudden cardiac death as a potential cause of sudden unexpected death in epilepsy. Here, we investigated the effects of carbamazepine (CBZ), lamotrigine (LTG), and levetiracetam (LEV) alone and in combination on the shortening properties of isolated ventricular cardiomyocytes of wild-type mice. Methods Properties of murine cardiomyocytes were determined by recording the sarcomere shortening with a video imaging system before, during, and after administration of AEDs in different concentrations and combinations. We assessed (i) the number of successful shortenings during continuous electrical stimulation (electromechanical coupling) and (ii) the shortening amplitude as well as other shortening-related properties upon repetitive electrical stimulation at 4 Hz. Data are given as mean ± SEM. Results At 100 μM, CBZ (10 cells), LTG (11 cells), and LEV (11 cells) alone had no effect on the electromechanical coupling but reversibly reduced shortening amplitudes by 15 ± 4, 24 ± 3, and 11 ± 3%, respectively. Increasing the LTG concentration to 250 (21 cells) and 500 μM (4 cells) reversibly inhibited the electromechanical coupling in 62 and 100% of the experiments. Importantly, simultaneous application of CBZ, LTG, and LEV at 100 μM also impaired the electromechanical coupling in 8 of 19 cardiomyocytes (42%) and reduced the shortening amplitude by 21 ± 4%. Conclusion Our data show that AEDs reversibly impair cardiac excitation and contraction. Importantly, the blocking effect on electromechanical coupling appears to be additive when different AEDs are simultaneously applied. The translational value of these experimental findings into clinical practice is limited. Our results, however, suggest that rationale AED therapy may be important with respect to cardiac side effects and potential facilitation of serious cardiac dysfunction especially when AEDs are used in combination or at very high doses.